(untitled) (Ustozlar uchun, 2026)
The causative agent of the new coronavirus infection SARS-CoV-2 is the pathogen responsible for the development of COVID-19, it is a multi-organ disease with a wide range of symptoms.[1,6,7] The completion of the acute phase of coronavirus infection varies in duration. This can be learned from dynamic monitoring of millions of patients who have been ill over the past 2 years. In a third of patients, the acute inflammatory period of the disease can pass without any consequences.[